2022
DOI: 10.5194/egusphere-egu22-8166
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unveiling Convective Momentum Transport at different scales during EUREC4A

Abstract: <p>The transport of horizontal momentum takes place at various spatial and temporal scales: from small-scale turbulence to cloud- and meso-scale circulations. This study focuses on the role of convective momentum transport (CMT) in the momentum budget in trade-wind cloud regimes with different patterns of cloud organization. Observations of the momentum budget during EUREC4A suggest that in early February, deeper convection and larger cloud structures are associated with a different profile of ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Another use of the ensemble is as a benchmark for convective parameterizations for GCMs, since the task of such parameterizations is to compute cloud properties from vertical profiles of the model's prognostic variables. Finally, we see Cloud Botany as sitting on the abstract side of a spectrum of modeling approaches, which include simulation setups under time‐varying forcings derived from a numerical weather prediction model (Savazzi, Nuijens, de Rooy, & Siebesma, 2022), on the lateral boundaries of open domains (Dauhut et al., 2022), Lagrangian LES (Narenpitak et al., 2021), mesoscale models with parameterized convection (Beucher et al., 2022) and regional and global models with partially resolved convection (Schulz & Stevens, 2023; Stevens et al., 2019). All these will be needed to fully elucidate the subtleties that govern the interactions between clouds, their environment and climate at the trade‐wind mesoscales.…”
Section: Discussionmentioning
confidence: 99%
“…Another use of the ensemble is as a benchmark for convective parameterizations for GCMs, since the task of such parameterizations is to compute cloud properties from vertical profiles of the model's prognostic variables. Finally, we see Cloud Botany as sitting on the abstract side of a spectrum of modeling approaches, which include simulation setups under time‐varying forcings derived from a numerical weather prediction model (Savazzi, Nuijens, de Rooy, & Siebesma, 2022), on the lateral boundaries of open domains (Dauhut et al., 2022), Lagrangian LES (Narenpitak et al., 2021), mesoscale models with parameterized convection (Beucher et al., 2022) and regional and global models with partially resolved convection (Schulz & Stevens, 2023; Stevens et al., 2019). All these will be needed to fully elucidate the subtleties that govern the interactions between clouds, their environment and climate at the trade‐wind mesoscales.…”
Section: Discussionmentioning
confidence: 99%
“…Their subcloud layer divergence under a cloud cluster opposes the subcloud-layer convergence otherwise observed (e.g. fig.12 ofSavazzi et al, 2024), perhaps disabling subcloud layer thermals from reaching cloud base and sustaining the convective heating pattern(Narenpitak et al, 2023). Such a mechanism, which relies on unconstrained warm rain microphysics schemes(Van Zanten et al, 2011), deserves further study.…”
mentioning
confidence: 86%
“…If nothing else, the difference emphasises that also other processes that can generate deeper, precipitating convection, such as aerosol concentrations, or dynamics associated with rain evaporation (Radtke et al, 2023), deserve consideration in explanations for SMOCs. More broadly, while we have here found that rain can help to create SMOCs, we have not studied rain evaporation dynamics, which might break them (Narenpitak et al, 2023), or even reverse their direction (Savazzi et al, 2023). Understanding what governs the lifetimes of SMOCs, and the shallow convective systems to which they couple, is a worthwhile topic of future research.…”
Section: Three Other Areas Of Focusmentioning
confidence: 90%
“…From the suite of realistically forced LESs of EUREC 4 A that are emerging (e.g. Dauhut et al, 2023;Saffin et al, 2023;Savazzi et al, 2023), we will focus on the regional simulations presented by Schulz and Stevens (2023). Run with the Icosahedral Nonhydrostatic (ICON) model in its large-eddy simulation configuration (Dipankar et al, 2015;Heinze 5.2 Observations & simulations 125 et al, 2017), these simulations represent the spatio-temporal extent of the campaign as realistically as possible.…”
Section: Icon Large-eddy Simulationsmentioning
confidence: 99%
See 1 more Smart Citation